2017
DOI: 10.1097/wno.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Venous Sinus Stenting in Idiopathic Intracranial Hypertension: Results of a Prospective Trial

Abstract: Stenting of VSS is safe and results in reduction of intracranial pressure in patients with IIH. This is associated with improvement in papilledema, RNFL thickness, VF parameters, and symptoms associated with intracranial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 29 publications
4
98
1
3
Order By: Relevance
“…The most common complication is recurrence of stenosis immediately proximal to the stent. Other complications include stent migration, in-stent thrombosis and, most concerning, intracranial hemorrhage 21 24. Dinkin et al 24 reported visual field improvement in patients with refractory IIH and fulminant visual loss following stenting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common complication is recurrence of stenosis immediately proximal to the stent. Other complications include stent migration, in-stent thrombosis and, most concerning, intracranial hemorrhage 21 24. Dinkin et al 24 reported visual field improvement in patients with refractory IIH and fulminant visual loss following stenting.…”
Section: Discussionmentioning
confidence: 99%
“…Other complications include stent migration, in-stent thrombosis and, most concerning, intracranial hemorrhage 21 24. Dinkin et al 24 reported visual field improvement in patients with refractory IIH and fulminant visual loss following stenting. In his study, visual field improvement was more remarkable than the one reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…VSS is becoming an increasingly used treatment option for intracranial venous stenosis in the setting of IIH and related pathologies 1 6 12. Although other therapies are available, VSS is a reasonable alternative that may address a key pathophysiologic component in patients with IIH, demonstrable venous sinus stenosis, and an associated trans-stenosis pressure gradient.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of magnetic resonance venography (MRV), venous sinus stenosis without thrombosis resulting in impaired CSF reabsorption may uncommonly be identified. Successful venous sinus stenting has been achieved in some adult patients refractory to medical treatment or presenting with imminent visual loss . Debate still remains regarding the role of venous sinus stenosis as a consequence rather than the cause of increased ICP.…”
Section: Pathogenesismentioning
confidence: 99%
“…Tetracyclines such as doxycycline and minocycline are still commonly used for the treatment of acne in adolescents and can lead to fulminant presentations of the disease (Fig. ).…”
Section: Secondary Causesmentioning
confidence: 99%